KONTRIBUSI MIGRAN TERHADAP PERTUMBUHAN SEKTOR INFORMAL DI PERKOTAAN (Kasus di Jakarta Selatan) - Sari Seftiani (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2010)
Migration Phenomenon in a big city can not be separated from informal sectorgrowth. Today, rural citizens are more proactive in reaching for opportunity andprosperity in the city that they wish by migration. Informal Sector happens when thelimited city to provide acceptable field of job. Limited job opportunity in formal sectorcauses the migrants have to choose the informal sector to look for prosperity. Thisstudy analyses the contribution of migrant, especially migrant in South Jakarta toinformal sector growth in this region by using qualitative approach. Research Resultshows that migrant, especially in South Jakarta, gives contribution to informal sectorgrowth in urban area.